Significações imaginárias sobre o cinema como experiências estéticas na formação inicial de professores - Pujol, Maristela Silveira (2019)
This dissertation is part of on line training, knowledge and Professional Development faculty member of the graduate program in education at the Universidade Federal de Santa Maria, RS. The research of problem of research about the imaginary meanings about the film as aesthetic experience in the training course in pedagogy. To this end, we seek to meet the imaginary meanings of pupils of the course of Pedagogy, the Federal University of Santa Maria, about the film device initial teacher Training; Identify the space cinema occupies in the life of students; identify the imaginary meanings of cinema students in education; identify the imaginary meanings of students on the national cinema in the classroom; recognize the imagination of students from their aesthetic experiences with cinema. From the qualitative research, under the Focal Group methodology based on the theory of Gatti (2005), four meetings were held with the participation of six undergraduate students, four girls and two boys. So, before their narratives, arising from the main themes addressed at each meeting; a questionnaire forwarded via e-mail and also of two short films, produced the study data. With the analysis, we can understand that the imaginary meanings of the group in front of the cinema, a lot comes from experiences gleaned from their life trajectories and their experiences as children, whether arising from the leisure time or that certain school shape echoed in adulthood. From the listener process sensitive lived for the duration of the meetings, students not only listened to each other, but they were able to understand how subject of a formative process that is formed in the presence of the other, the relationship both were established with the object of study, as with group exchanges. Discussions in front of listening in the classroom, listening to the pedagogical space, listening to the environments where the subjects are and, which are often ignored for the simple reason that there is no concern to make listening to the other, making up for an act individualistic, were present in the narratives of the study. Discussions about movies and those arising after the views of the two short films, resulted in the understanding that the cinema is in addition to a moment of leisure, of content developed connections in the classroom, or thematic discussions